Pengaruh Compensation dan Work Environment terhadap Turnover Intention Yang dimediasi oleh Job Satisfaction pada PT Bank Mandiri Taspen - Haula Syifa Utari; Andreas Wahyu Gunawan; Netania Emilisa; Aqsa Fadillah (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to analyze the effect of compensation and work environment on turnover intention mediated by job satisfaction at PT Bank Mandiri Taspen, which is a banking company with two different branches. This type of research uses a quantitative method by using the hypothesis testing method on two divisions in a banking company. The data collection technique used in this research is a questionnaire with 92 respondents. Data processing and analysis in this study used Structural Equation Modeling (SEM) with Partial Least Square (PLS) in the SmartPLS application. The results showed that: Compensation has a negative and significant effect on Turnover intention, Compensation has a positive and significant effect on Job satisfaction, Work environment has a negative and significant effect on Turnover intention, Work environment has a positive and significant effect on Job satisfaction, Job satisfaction has Negative and significant effect on Turnover intention, Compensation has a negative and significant effect on Turnover intention through Job satisfaction, Work environment has a negative and significant effect on Turnover intention. Job satisfaction has a positive influence on Job satisfaction because the more comfortable a work environment is, the employees will feel safe and comfortable in completing their work and Compensation and Work Environment are proven to be significant and have a negative effect based on the existing beta coefficient value which indicates that both these variables have an influence on Turnover Intention at PT Bank Mandiri Taspen